2009
DOI: 10.1378/chest.08-0980
|View full text |Cite
|
Sign up to set email alerts
|

Survival for Patients With HIV Admitted to the ICU Continues to Improve in the Current Era of Combination Antiretroviral Therapy

Abstract: Background-The highly active antiretroviral therapy (ART) era (1996-present) has been associated with improved survival among HIV-infected outpatients, but ICU data from 2000-present are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
171
5
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(197 citation statements)
references
References 27 publications
17
171
5
4
Order By: Relevance
“…The prognostic factors of mortality in HIV-infected patients admitted to the ICU are acute illness severity, poor functional status, low albumin rate, and respiratory failure requiring mechanical ventilation [47][48][49][50][51][52][53]. However, specific HIV characteristics (CD4 cell count, plasma HIV-RNA load, HIV-related diagnosis, or antiretroviral therapy) have not been clearly identified as predictors of ICU mortality [4,15,37,38,[49][50][51][52][54][55][56][57][58][59], although some reports have associated CD4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic factors of mortality in HIV-infected patients admitted to the ICU are acute illness severity, poor functional status, low albumin rate, and respiratory failure requiring mechanical ventilation [47][48][49][50][51][52][53]. However, specific HIV characteristics (CD4 cell count, plasma HIV-RNA load, HIV-related diagnosis, or antiretroviral therapy) have not been clearly identified as predictors of ICU mortality [4,15,37,38,[49][50][51][52][54][55][56][57][58][59], although some reports have associated CD4…”
Section: Discussionmentioning
confidence: 99%
“…However, specific HIV characteristics (CD4 cell count, plasma HIV-RNA load, HIV-related diagnosis, or antiretroviral therapy) have not been clearly identified as predictors of ICU mortality [4,15,37,38,[49][50][51][52][54][55][56][57][58][59], although some reports have associated CD4…”
Section: Discussionmentioning
confidence: 99%
“…Further studies, connected with the introduction of HAART, have demonstrated improved survival, even amongst PCP patients [7,8]. At present, respiratory failure is still the most common indication for ICU admission [9,10], although PCP as a cause of respiratory failure is substantially less common. After the introduction of HAART, the number of hospitalizations related to AIDS decreased, while the incidence of sepsis as a reason for ICU admission increased [11].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Hospital admission patterns for patients with HIV have changed in the modern antiretroviral therapy era. 2,10,11 Patients are less likely to be hospitalized for AIDS-related opportunistic infections.…”
Section: Introductionmentioning
confidence: 99%